Trends in developing metaheuristics, algorithms, and optimization approaches - Yin, Peng-Yeng, 1966-; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'This book provides insight on the latest advances and analysis of technologies in metaheuristics computing, offering widespread coverage on topics such as genetic algorithms, differential evolution, and ant colony optimization'--Provided by publisher.
A novel particle swarm optimization algorithm for multi-objective combinatorial optimization problem / Rahul Roy, Satchidananda Dehuri, Sung Bae Cho -- A hybrid simulated annealing and simplex method for fixed-cost capacitated multicommodity network design / Masoud Yaghini ... [et al.] -- A hybrid meta-heuristic algorithm for dynamic spectrum management in multiuser systems: combining simulated annealing and non-linear Simplex Nelder-Mead / Hernan X. Cordova, Leo Van Biesen -- Discrete artificial bee colony optimization algorithm for financial classification problems / Yannis Marinakis ... [et al.] -- Vector evaluated and objective switching approaches of artificial bee colony algorithm (ABC) for multi-objective design optimization of composite plate structures / S. N. Omkar ... [et al.] -- An ant colony system algorithm for the hybrid flow-shop scheduling problem / Safa Khalouli, Fatima Ghedjati, Abdelaziz Hamzaoui -- Discrete particle swarm optimization for the multi-level lot-sizing problem / Laurent Deroussi, David Lemoine -- Adaptive non-uniform particle swarm application to plasmonic design / Sameh Kessentini ... [et al.] -- New evolutionary algorithm based on 2-opt local search to solve the vehicle routing problem with private fleet and common Carrier / Jalel Euchi, Habib Chabchoub, Adnan Yassine -- Scatter search applied to the vehicle routing problem with simultaneous delivery and pickup / Gladys Maquera ... [et al.] -- Parallel scatter search algorithms for exam timetabling / Nashat Mansour, Ghia Sleiman-Haidar -- Pseudo-cut strategies for global optimization / Fred Glover ... [et al.] -- Management of bus driver duties using data mining / Walid Moudani, Fix Mora-Camino -- A new approach to associative classification based on binary multi-objective particle swarm optimization / Madhabananda Das ... [et al.] -- Extraction of target user group from web usage data using evolutionary biclustering approach / R. Rathipriya, K. Thangavel, J. Bagyamani -- Dynamic assignment of crew reserve in airlines / Walid Moudani, Fix Mora-Camino -- DIMMA-implemented metaheuristics for finding shortest hamiltonian path between iranian cities using sequential DOE approach for parameters tuning / Masoud Yaghini, Mohsen Momeni, Mohammadreza Sarmadi.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed August 23, 2012).
Keywords: Heuristic algorithms; Computer simulation; Combinatorial optimization; Computational intelligence; Ant colony optimization; Differential evolution; Genetic algorithm; GRASP; Greedy algorithm; Hybrid method; Hyper-heuristics.; Metaheuristics; Strategic oscillation; Tabu search; Variable neighborhood search